Assessing the Performance of Value – at – Risk Models in Hang Seng Index and China Securities Index - LI, VIVIANA (2012)
Abstract: In the paper, we investigate the relative performance of different Value at Risk ( VaR ) models with the log returns of China(CSI300) and Hong Kong(HSI) stock index prior to and during the financial crisis. In addition to wider the range of VaR models we study the behaviour of Historical simulation, Hull- White ( Historical Simulation with volatility adjustement), Unconditional Extreme Value Thoery ( including GPD and GEV), conditional EVT and Hybird Historical Simulation (HHS)models to generate 95% confidence level estimates. Backtest including Kupiec test, independent test and Blanco and Ihle Test are used. Results show that none of the model can capture the Asian Financial Crisis by using Hang Seng Index. However, both CGPD and HHS model are able to capture the extreme events.